2021
DOI: 10.3390/en14051420
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Voltage DC Backbone with Aggregated RES and BESS: Benefits Compared to a Traditional Low-Voltage AC System

Abstract: The increasing penetration of PV into the distribution grid leads to congestion, causing detrimental power quality issues. Moreover, the multiple small photovoltaic (PV) systems and battery energy storage systems (BESSs) result in increasing conversion losses. A low-voltage DC (LVDC) backbone to interconnect these assets would decrease the conversion losses and is a promising solution for a more optimal integration of PV systems. The multiple small PV systems can be replaced by shared assets with large common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The latter connects the LVDC backbone through a central DC/AC inverter to the point of common coupling (PCC) of the AC microgrid, further referred to as the single point of connection (SPoC). Another finding of the referred study [9] is that conversion losses in the proposed architecture can decrease significantly-up to 12 percentage points-compared to a traditional AC microgrid. This is mainly driven by the favourable system voltages which led to a lower voltage ratio and hence lower conduction and switching losses of the converter.…”
Section: Research In the Field Of Lvdc Backbonesmentioning
confidence: 86%
See 1 more Smart Citation
“…The latter connects the LVDC backbone through a central DC/AC inverter to the point of common coupling (PCC) of the AC microgrid, further referred to as the single point of connection (SPoC). Another finding of the referred study [9] is that conversion losses in the proposed architecture can decrease significantly-up to 12 percentage points-compared to a traditional AC microgrid. This is mainly driven by the favourable system voltages which led to a lower voltage ratio and hence lower conduction and switching losses of the converter.…”
Section: Research In the Field Of Lvdc Backbonesmentioning
confidence: 86%
“…In that context, previous research has demonstrated that an LVDC backbone architecture benefits from multiple advantages for energy communities centred on a single feeder [9]. LVDC backbones consist of aggregated PV systems and a central BESS.…”
Section: Research In the Field Of Lvdc Backbonesmentioning
confidence: 99%
“…charging stations for e-mobility or computer systems, operate on a DC basis. The interconnection of these components in DC microgrids, which are typically operated as subsystems of AC grids, avoids unnecessary dc-ac and AC-DC conversion and enables a cost-efficient subgrid design as well as an increased self-consumption of renewable energies, see Azaioud et al (2021). An essential element for the reliable design and operation of LVDC microgrids is the preservation of network stability.…”
Section: Stability Of Lvdc Networkmentioning
confidence: 99%
“…Primitive impedance matrices or series impedances form the foundation for modelling distribution networks. Unbalance analysis or harmonic inspection, as well as simulations of the impact RES generates on distribution networks [19,[24][25][26][27] necessitate accurate modelling of the lines in order to produce accurate results. While calculating the primitive impedance matrix, geometrical parameters are important.…”
Section: Cable Geometry Determinationmentioning
confidence: 99%